Diffraction‐based determination of single‐crystal elastic constants of polycrystalline titanium alloys. Issue 5 (20th September 2019) - Heldmann, Alexander; Hoelzel, Markus; Hofmann, Michael; Gan, Weimin; Schmahl, Wolfgang W.; Griesshaber, Erika; Hansen, Thomas; Schell, Norbert; Petry, Winfried
Abstract : The single‐crystal elastic constants of polycrystalline titanium alloys have been determined using neutron and synchrotron powder diffraction. Abstract : Single‐crystal elastic constants have been derived by lattice strain measurements using neutron diffraction on polycrystalline Ti‐6Al‐4V, Ti‐6Al‐2Sn‐4Zr‐6Mo and Ti‐3Al‐8V‐6Cr‐4Zr‐4Mo alloy samples. A variety of model approximations for the grain‐to‐grain interactions, namely approaches by Voigt, Reuss, Hill, Kroener, de Wit and Matthies, including texture weightings, have been applied and compared. A load‐transfer approach for multiphase alloys was also implemented and the results are compared with single‐phase data. For the materials under investigation, the results for multiphase alloys agree well with the results for single‐phase materials in the corresponding phases. In this respect, all eight elastic constants in the dual‐phase Ti‐6Al‐2Sn‐4Zr‐6Mo alloy have been derived for the first time.